1990
DOI: 10.1115/1.2904392
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Investigation Into the Effects of Pressure, Subcooling, Surface Augmentation and Choice of Coolant on Pool Boiling in the Design of Cooling Systems for High-Power-Density Electronic Chips

Abstract: A high power electronic chip was simulated experimentally to investigate upper cooling capabilities using a variety of pool boiling enhancement techniques. Parametric effects of system pressure, subcooling, surface augmentation, and choice of coolant on boiling heat transfer from a vertical 12.7 × 12.7 mm2 flat surface were examined. The two fluorocarbon coolants tested, FC-72 and FC-87, resulted in similar boiling curves, but FC-87 significantly reduced chip surface temperature for a given heat flux. Increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(32 citation statements)
references
References 7 publications
8
24
0
Order By: Relevance
“…This tends to decrease the number of active bubble nucleation sites and increases the wall superheat which allows bubbles to depart from the surface. This is further supported for various liquids by other researchers [16][17][18][19]. Various authors [14,16,17,[19][20][21][22] reported that CHF also shows an increasing trend with increasing pressure.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…This tends to decrease the number of active bubble nucleation sites and increases the wall superheat which allows bubbles to depart from the surface. This is further supported for various liquids by other researchers [16][17][18][19]. Various authors [14,16,17,[19][20][21][22] reported that CHF also shows an increasing trend with increasing pressure.…”
Section: Introductionsupporting
confidence: 54%
“…This is further supported for various liquids by other researchers [16][17][18][19]. Various authors [14,16,17,[19][20][21][22] reported that CHF also shows an increasing trend with increasing pressure. Mudawar and Anderson [19] reported that an increase in pressure results in higher values of CHF using water as the working fluid.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Recent studies (see [5]) have demonstrated various means of enhancing the performance of thermosyphons including: 1) geometrically modifying the chip surface (surface enhancement), 2) subcooling the coolant to a temperature well below the boiling point, and 3) increasing coolant pressure.…”
Section: A Pool Boiling/thermosyphonsmentioning
confidence: 99%
“…They include micro-texturing the surface with cavities and features whose size and shape are configured relative to the contact angle and thermophysical properties of the coolant [3], [8]- [14]. A second form of surface enhancement is machining of mini-structures (e.g., mini-grooves and mini-studs) which both help sustain the bubble nucleation and increase the surface area available for boiling [3], [5], [15]. The third method of enhancement consists of bonding a relatively large extended surface onto the device surface for the purpose of greatly increasing the heat transfer area, provided the conduction resistance associated with the heat sink does not increase the device temperature appreciably [15], [16].…”
Section: A Pool Boiling/thermosyphonsmentioning
confidence: 99%